1995
DOI: 10.1007/bf01203864
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic adenosine monophosphate agonist elevates the b- and c-waves of the rabbit direct-current electroretinogram

Abstract: The effects of the stable cyclic adenosine monophosphate analogue adenosine 3',5'-cyclic monophosphorothioate Sp-isomer (Sp-cAMPS) on the direct-current electroretinogram and the standing potential of the eye were studied. Corneal recordings were obtained from unilaterally vitrectomized albino rabbit eyes during alternating intravitreal perfusions with Sp-cAMPS and a control solution (Pharmacia eye irrigating solution). The contralateral eye was used as a control. To evaluate further the effects on the c-wave,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There is evidence that cAMP signaling contributes to both ON and OFF cone bipolar cell signaling (Bragadottir and Jarkman, 1995, Maguire and Werblin, 1994). Immunohistochemical evidence demonstrated that PKA type II is selectively localized to a subtype of cone bipolar cells, type 3b, whereas HCN4 selectively labeled type 3a cone bipolar cells (Mataruga et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that cAMP signaling contributes to both ON and OFF cone bipolar cell signaling (Bragadottir and Jarkman, 1995, Maguire and Werblin, 1994). Immunohistochemical evidence demonstrated that PKA type II is selectively localized to a subtype of cone bipolar cells, type 3b, whereas HCN4 selectively labeled type 3a cone bipolar cells (Mataruga et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that some cone bipolar cells, which can be identified using PKA, contribute to the rod driven pathway (Mataruga et al, 2007). There is also evidence that cAMP contributes to both OFF and ON cone pathways (Bragadottir and Jarkman, 1995, Maguire and Werblin, 1994). …”
Section: Discussionmentioning
confidence: 99%